Public Service Broadcasting Online - Brevini, B. author. aut Link
XIV, 200 p.
Keywords: This book investigates the extent to which a Public Service Broadcasting (PSB) ethos has been extended to the online world in Europe. It examines the most significant policy initiatives carried out by PSBs in Europe on online platforms, and analyzes how the public service philosophy is being reinvented by policy makers.